QUESTIONING THE SMALL-CLAIMS COURT IN INDONESIA IN THE FRAMEWORK OF NATIONAL CIVIL PROCEDURAL LAW REFORM - Anita Afriana; isis Ikhwansyah (Jurnal Dinamika Hukum, 2016)
One of the alternatives to renew the law is by forming regulations and the litigation institutions that can accommodate the society. In private litigation proceeding, manifestation of ideas in litigation reform can be seen through by the Supreme Court Regulation (PerMA) No. 2 Year 2015. This fast procedural mechanism is called small claims court (SCC). This article discusses the effectiveness of SCC implementation in Indonesia as one of the states that enacts civil law system, and its regulation in order to renew civil law procedures. Research methodology used juridical-normative while the results show that SCC is effectively enacted in Indonesia. The prevailing regulation currently in PerMA is to fill the gap of law, considering that the legislation process takes time to establish an act. Thus, it is best for Indonesia to establish SCC within a certain act in the future, to pursue the unification of law within the regime of private law procedures.Keywords : effectiveness, civil law, small-claims court, renewal of law